2006
DOI: 10.1007/s10653-005-9009-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for safety of soils and vegetables around a lead/zinc mine

Abstract: Concentrations of heavy metals (Pb, Zn, Cd, Cu) were determined in soils and vegetables (chrysanthemum, spinach and four cultivars of Chinese cabbage from the area adjacent to a Pb/Zn mine in Shaoxing, Zhejiang province, China, and compared with the Chinese National Standards for Soil Environmental Quality. The accumulation of heavy metals in cabbage cv. Siyuegreen was investigated at different distances from the center of the mine. The vegetable plantation soils were polluted with Pb, Cd, Cu and Zn, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 11 publications
0
40
1
Order By: Relevance
“…Based on an average vegetable consumption of 0.5 kg day −1 per adult, the consumption of most vegetables listed in Table 3 would exceed the acceptable daily intake of phthalic acid esters compared to the tolerable daily intake (37 μg kg ) recommended by the US Environmental Protection Agency (Koch et al 2003). It is suggested that vegetables grown in contaminated soils could be considered as potentially contaminated (Li et al 2006a). Therefore, to minimize phthalic acid ester accumulation in vegetables, the use of film and agricultural chemicals containing phthalic acid esters should be avoided and vegetables should not be grown in industrial areas.…”
Section: Effect and Accumulation Of Phthalic Acid Esters In Vegetablesmentioning
confidence: 99%
“…Based on an average vegetable consumption of 0.5 kg day −1 per adult, the consumption of most vegetables listed in Table 3 would exceed the acceptable daily intake of phthalic acid esters compared to the tolerable daily intake (37 μg kg ) recommended by the US Environmental Protection Agency (Koch et al 2003). It is suggested that vegetables grown in contaminated soils could be considered as potentially contaminated (Li et al 2006a). Therefore, to minimize phthalic acid ester accumulation in vegetables, the use of film and agricultural chemicals containing phthalic acid esters should be avoided and vegetables should not be grown in industrial areas.…”
Section: Effect and Accumulation Of Phthalic Acid Esters In Vegetablesmentioning
confidence: 99%
“…Many countries have regulatory guidelines for heavy-metal presence and exposure as well as remediation and treatment options. Screening of soil and water sources is conducted frequently to prevent overconsumption, but many of these programs and technologies are not readily available in developing nations (Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable is an important part of the human diet in China (Zheng et al, 2007). It is believed that vegetables can become contaminated with HMs if they grow on soils contaminated by mining, vehicular exhaust, industrial activities and other agriculture activities (Cui et al, 2004;Li et al, 2006a). The levels of HMs in vegetables and soils and their risk to people are of great public concern (Li et al, 2006b;Wang et al, 2008Wang et al, , 2005Xie et al, 2006).…”
Section: Introductionmentioning
confidence: 99%